Flexible non-greedy discriminant subspace feature extraction. (August 2019) - Zhao, Henghao; Fu, Liyong; Gao, Zhigang; Ye, Qiaolin; Yang, Zhangjing; Yang, Xubing
Abstract: Recently, L 1 -norm-based non-greedy linear discriminant analysis (NLDA-L 1 ) for feature extraction has been shown to be effective for dimensionality reduction, which obtains projection vectors by a non-greedy algorithm. However, it usually acquires unsatisfactory performances due to the utilization of L 1 -norm distance measurement. Therefore, in this brief paper, we propose a flexible non-greedy discriminant subspace feature extraction method, which is an extension of NLDA-L 1 by maximizing the ratio of L p -norm inter-class dispersion to intra-class dispersion. Besides, we put forward a powerful iterative algorithm to solve the resulted objective function and also conduct theoretical analysis on the algorithm. Finally, experimental results on image databases show the effectiveness of our method